Blockchain; a new accounting paradigm to anticipate bankruptcy - BELATIK , Manal (Revue du contrôle, de la comptabilité et de l’audit, 2023)
Blockchain technology and its many applications have become a major catalyst for new ideas and solutions for the financial sector. But the theoretical framework of Blockchain, even for the financial sector, remains rough and empirical evidence is lacking. The objective of our paper is to show how Blockchain based accounting could anticipate the bankruptcy of a company to do this we will model the quarterly fluctuations of the 2 famous bankruptcy prediction models; ZScore and Merton’s DD of general accounting and compare them to the daily fluctuations of Blockchain’s real time accounting. A case study was chosen as a research strategy to add a realistic touch. There are two main outcomes of our research. The first is that the technology will therefore have greater implications for companies with high volatility. The second finding is that the implications will not only be positive in the form of earlier identification of difficulties but may also negatively affect the company by exacerbating the short-term economic problem, the problem that has not been discussed in the context of Blockchain accounting before.